Traumatic interspecific interaction between a sting ray and a false killer whale (Pseudorca crassidens) - Arbelo Hernández, Manuel Antonio; Sierra Pulpillo, Eva María; Martín, Vidal; Tejedor, Marisa; Bernaldo De Quirós Miranda, Yara; Andrada Borzollino, Marisa Ana; Fernández Rodríguez, Antonio Jesús (2011)
We report the case of a subadult male specimen (246 cm length) of false killer whale (Pseudorca crassidens) stranded alive on the beach of Papagayo, Lanzarote (Canary Islands). The animal was attended on the beach by tourists who tried to return it to the sea, the animal beached again and died. It was later transferred to the facilities of the Canary Cetacean Museum (Puerto Calero, Lanzarote), dependent on the Society for the Study of Cetaceans in the Canary Archipelago, where a complete necropsy was performed on the same day. The animal showed a poor nutritional status. Among the external lesions we highlight the presence of a large shark bite around the perimeter of the dorsal fin with associated hemorrhages in the tissue of the wound edges affecting skin, subcutaneous and muscular planes. Epaxial skeletal muscle showed marked atrophy. Aditionally, generalized atrophy, mixed multifocal myositis, severe degenerative changes, segmental hypercontraction and contraction band necrosis in fibers of smaller caliber were observed microscopically. The main macroscopic finding found was the presence of a ray sting causing a deep penetrating wound from the ventral surface through the right dorsal area of the tongue affecting the ceiling of the oral cavity in its caudal region (soft palate) with severe inflammatory reaction. Microscopic examination showed a necrotic and pyogranulomatous glossitis and stomatitis associated with a foreign body trauma and bacterial secondary infection. To our knowledge this is the first case of traumatic interspecific interaction affecting a false killer whale and a sting ray (only described in bottlenose dolphin and killer whale). Injuries resulting from the sting in the tongue and the oral cavity caused the inability of the animal to continue feeding provoking weight loss and progressive weakness and leading subsequently to the incidents of sharks attacks, stranding and finally, death of the animal.